HUBUNGAN PELIBATAN KELUARGA TERHADAP KEMAMPUAN PENDIDIKAN SOSIAL FINANSIAL ANAK USIA 5-6 TAHUN - Fifiet Dwi Tresna Santana; Ifat Fatimah Zahro (Generasi Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2020)
Social and financial education is very appropriate to be carried out from an early age to prepare their financial management skills in the future so that they are not trapped in a consumptive lifestyle. This research is to find out the involvement of parents in the ability of social financial education between the ages of 5-6 years of Cimahi PAUD by using correlational quantitative research methods. Students and parents at Al-Marhamah Kindergarten, Cimahi City, were the subjects of research applying social financial education. Data were collected using observation, interviews, and questionnaires, then the product-moment correlation was analyzed through the SPSS program. The results revealed a relationship between the variables of parental involvement with financial social education, it is known that the correlation of 0.684 and the significance of 0.04 <0.05, it can be concluded that there is a positive and significant relationship between parental involvement of students with financial social education of children. A correlation value of 0.684 which means a strong relationship and has a contribution of 46.79%.